Pattern of Coagulopathy and Their Association with Mortality in COVID-19 Patients in Makkah, KSA - Imran Nazir, Syed Majid Hamid, Abdul Shakoor, Rizwan Rasul Khan, Muhammad Ajmal Farid, Iffat Imran, Mohammed Ali Al Zubaidi, Khalid Khalil (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the pattern of coagulation profile and their association with mortality in COVID-19 patients. Study Design: Retrospective descriptive study Place and Duration of Study: Makkah, Saudi Arabia from 2nd March 2020, to 2nd July 2020. Methodology: One thousand, nine hundred and twenty three conceded COVID-19 patients affirmed with polymerase chain response testing were included. Results: Patients’ average age was 58.7±2.75 years. Patients drop was observed 6.4% in the survivor group as compared to 0.8% in the non-survivor group with a significant (p=0.000) association with mortality. Prolonged PT/INR was observed in 16% of patients, having a significant association (P=0.003) with mortality. APTT was prolonged in 29.4% of patients, and a comparison of APTT levels between the survivor and non-survivor groups showed a significant difference (p=0.002. A higher fibrinogen level was seen in 23.2% of patients with a significant (p=0.001). Conclusion: Severe COVID-19 infection is related to coagulopathy that is related to the destitute condition of hospitalized patients. Early and consistent evaluation of the coagulation profile along the disease course can help to treat and prevent disease morbidity and mortality in the hospital setting.